OPTIMASI PROSES EKSTRAKSI GINGEROL DARI RIMPANG JAHE SEGAR MENGGUNAKAN PELARUT n-HEXANE SECARA BATCH - Fitra Pradhita; Margaretha Praba Aulia; H Hargono (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Ginger contains gingerol which is very useful in the industry. Gingerol can be used in the crosslinking of starch to crosslinking the carbon chains in the starch. Gingerol on the market are still rare, expensive and of poor quality, so it needs to be studied gingerol extraction method to efficiently generate high-quality gingerol. This study aims to determine the most influential variables between solvent feed ratio, particle size ginger, temperature and look for the optimum operating conditions on the extraction of gingerol from fresh ginger rhizome. This study is planned by the method of factorial design two levels and three independent variables are: temperature (50 and 60 °C), particle size (10x10x1 mm and 5x5x1 mm), solvent feed ratio (1:6 and 1:4 g / ml solvent) . Dependent variable used is the volume of n-hexane 300 ml technical, stirring speed of 450 rpm and extraction time 1hr with sampling every 10 minutes. 3 variables show a positive influence / improve gingerol obtained and solvent feed ratio is the most influential. Optimum conditions in the extraction process is at a temperature of 60 ° C gingerol, 5x5x1 mm particle size, and solvent feed ratio of 1:4 g / ml solvent.